PERSEPSI GURU TENTANG PENGAWASAN PELAKSANAAN TUGAS GURU OLEH KEPALA SEKOLAH DI SEKOLAH MENENGAH KEJURUAN NEGERI (SMK N) KECAMATAN LUBUK BASUNG - Eka Putri (Jurnal Bahana Manajemen Pendidikan, 2015)
This article aims to obtain information about the perception of teachers on the controlling of teachers task implementation by principals at SMK N  Kecamatan Lubuk Basung. This is a descriptive research with a population 150 people. The research sample is determined using proportional random sampling technique which numbered 45 people. The research instrument was questionnaire in the form of Likert Scale, which has proven its validity and reliability. Research data processing performed by using the average formula (mean). In general, the result of the research is the perception of teachers on the controlling of teachers task implementation by principals at SMK N Kecamatan Lubuk Basung is good with an totality score 3,75.Keyword: controlling, task implementation